Validation of Open-Heart Intraoperative Risk score to predict a prolonged intensive care unit stay for adult patients undergoing cardiac surgery with cardiopulmonary bypass - Tribuddharat S; Sathitkarnmanee T; Ngamsaengsirisup K; Wongbuddha C (Dove Medical Press, 2018)
Sirirat Tribuddharat,1 Thepakorn Sathitkarnmanee,1 Kriangsak Ngamsaengsirisup,1 Chawalit Wongbuddha2 1Department of Anesthesiology, 2Division of Cardiothoracic Surgery, Department of Surgery, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand Background: A prolonged stay in an intensive care unit (ICU) after cardiac surgery with cardiopulmonary bypass (CPB) increases the cost of care as well as morbidity and mortality. Several predictive models aim at identifying patients at risk of prolonged ICU stay after cardiac surgery with CPB, but almost all of them involve a preoperative assessment for proper resource management, while one – the Open-Heart Intraoperative Risk (OHIR) score – focuses on intraoperative manipulatable risk factors for improving anesthetic care and patient outcome.Objective: We aimed to revalidate the OHIR score in a different context.Materials and methods: The ability of the OHIR score to predict a prolonged ICU stay was assessed in 123 adults undergoing cardiac surgery (both coronary bypass graft and valvular surgery) with CPB at two tertiary university hospitals between January 2013 and December 2014. The criteria for a prolonged ICU stay matched a previous study (ie, a stay longer than the median).Results: The area under the receiver operating characteristic curve of the OHIR score to predict a prolonged ICU stay was 0.95 (95% confidence interval 0.90–1.00). The respective sensitivity, specificity, positive predictive value, and accuracy of an OHIR score of ≥3 to discriminate a prolonged ICU stay was 93.10%, 98.46%, 98.18%, and 95.9%.Conclusion: The OHIR score is highly predictive of a prolonged ICU stay among intraoperative patients undergoing cardiac surgery with CPB. The OHIR comprises of six risk factors, five of which are manipulatable intraoperatively. The OHIR can be used to identify patients at risk as well as to improve the outcome of those patients. Keywords: predictive models, validation studies, cardiac surgical procedures, cardiopulmonary bypass, intensive care units, OHIR score